Approximate quasi-orthogonality of operator algebras and relative quantum privacy. Issue 2 (April 2021) - Kribs, David W.; Levick, Jeremy; Nelson, Mike; Pereira, Rajesh; Rahaman, Mizanur
Abstract : We show that the approximate quasi-orthogonality of two operator algebras is equivalent to the algebras being approximately private relative to their conditional expectation quantum channels. Our analysis is based on a characterization of the measure of orthogonality in terms of Choi matrices and Kraus operators for completely positive maps. We present examples drawn from different areas of quantum information.